Rare earth doped Cu-Al2O3 nano dispersion strengthened alloy and preparation method thereof

By doping Cu-Al2O3 nanodispersion reinforced alloy with rare earth doping, the distribution of Al2O3 nanoparticles and the role of rare earth elements are regulated, and the problem of insufficient conductivity of traditional Cu-Al2O3 alloy is solved, achieving breakthrough in conductivity, strength and heat resistance. promote.

CN119242980APending Publication Date: 2025-01-03CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411220911.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The conductivity of Cu-Al2O3 alloy materials prepared by traditional internal oxidation method cannot break through the 100% IACS bottleneck, resulting in limitations in the high-temperature softening performance and application fields.

Method used

Rare-earth doped Cu-Al2O3 nanodispersion reinforced alloy is used to regulate the distribution of Al2O3 nanoparticles and the role of rare earth elements by reasonably designing the Al content and the addition of rare earth elements Ce, La, and Sr, so as to improve the conductivity and avoid the formation of microcracks.

Benefits of technology

The conductivity of the alloy is significantly improved to 100.3 IACS, enhanced strength and heat resistance, improved plasticity and airtightness, and broke through the conductivity bottleneck of traditional Cu-Al2O3 alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005023000610000131
    Figure BDA0005023000610000131
  • Figure BDA0005023000610000151
    Figure BDA0005023000610000151
  • Figure BDA0005023000610000161
    Figure BDA0005023000610000161
Patent Text Reader

Abstract

The invention provides a rare earth doped Cu-Al2O3 nano dispersion strengthened alloy and a preparation method of the rare earth doped Cu-Al2O3 nano dispersion strengthened alloy. The rare earth doped Cu-Al2O3 nano dispersion strengthened alloy disclosed by the invention is prepared from the following components in percentage by weight: 0.01 wt% to 0.08 wt% of Al2O3, 0.01 wt% to 0.03 wt% of Ce, 0.01 wt% to 0.03 wt% of Sr, 0.01 wt% to 0.03 wt% of La and the balance of copper. The conductivity of the alloy is remarkably improved and reaches 100.3 IACS, and the bottleneck that the conductivity of a Cu-Al2O3 alloy material produced by an internal oxidation method reaches 100% IACS is broken through. The invention further provides a preparation method of the rare earth doped Cu-Al2O3 nano dispersion strengthened alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloys, and in particular relates to a rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy and a preparation method thereof. Background Art

[0002] Pure copper has excellent electrical and thermal conductivity, but after annealing at 900℃, the yield strength of pure copper is low, between 25-50MPa. Due to its low yield strength, it is easy to deform during service, affecting the stability and safety of the device. In recent years, the solid solution strengthened or low solute content aging strengthened high-conductivity copper alloys such as Cu-Zr and Cu-Ag have been developed. The conductivity is between 90-95% IACS. After annealing at 900℃, σ 0.2 Between 50-100Mpa, although the yield strength is improved, its absolute conductivity is low. Age-strengthening high-solute copper alloys, such as Cu-Cr-Zr, Cu-Ni-Si, Cu-Fe-P, etc., after combined deformation heat treatment, strength: σ b =500-800MPa,σ 0.2 =450-750MPa, electrical conductivity is about 50-80%IACS. After annealing at 900℃, the strength and electrical conductivity of the alloy drop sharply, and the electrical conductivity is about 25-50%IACS. Others such as beryllium bronze, ordinary brass, bronze, etc. have electrical conductivity of about 10-40%IACS.

[0003] Nano-dispersion strengthened copper alloy is a kind of high-strength and high-conductivity copper alloy with excellent resistance to high-temperature softening. It is widely used because of its excellent comprehensive performance. The preparation process of Cu-Al2O3 dispersion strengthened copper alloy prepared by internal oxidation method includes: alloy composition design, atomization powder making, powder screening, internal oxidation, crushing, reduction, jacketing, hot extrusion, cold processing and other processes. The characteristic of internal oxidation is to place Cu-Al alloy powder in an oxygen source and oxidize it under the protection of high-temperature inert gas. At this time, the ideal internal oxidation structure is: Cu in Cu-Al alloy powder becomes Cu X O, Al becomes Al2O3, the internal oxidation powder is crushed and reduced in a high temperature hydrogen environment, Cu X O turns into Cu, Al2O3 does not change, and Cu X The lower the content of O, the better. Some preparation technologies of Cu-Al2O3 alloys are disclosed in the related art, among which the typical patents are: CN101240387B, CN109536771B, US9447484B2, etc. In the above methods, Cu-Al2O3 alloy powder or powder ingot is processed into dense Cu-Al2O3 alloy material through subsequent processes such as hot extrusion.

[0004] However, in the process of preparing Cu-Al2O3 by traditional internal oxidation, a large amount of coarse copper aluminate (CuAlO2) distributed along the particle surface will be produced during the atomization powder making and internal oxidation process. It has high stability and cannot be reduced by hydrogen, resulting in cracking of the final alloy rod during red punching or cold working, producing micro cracks, resulting in a significant reduction in air tightness. Moreover, the electrical conductivity of Cu-Al2O3 alloy materials produced by traditional internal oxidation method cannot break through the bottleneck of 100% IACS, which restricts its application in the fields of large-scale integrated circuit lead frames, various cavities of electric vacuum devices, high-power heat sinks, etc. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy, which significantly improves the electrical conductivity of the alloy to 100.3IACS, breaking through the bottleneck of the electrical conductivity of the Cu-Al2O3 alloy material produced by the internal oxidation method reaching 100%IACS.

[0006] The invention also provides a method for preparing a rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy.

[0007] The first aspect of the present invention provides a rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy, the components of which include:

[0008] Al2O3: 0.01wt%~0.08wt%,

[0009] Ce: 0.01wt%~0.03wt%,

[0010] Sr: 0.01wt%~0.03wt%,

[0011] La: 0.01 wt% to 0.03 wt%,

[0012] The balance is copper and unavoidable impurities.

[0013] The present invention relates to a technical solution for rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy, which has at least the following characteristics:

[0014] Beneficial effects:

[0015] The present invention regulates the volume percentage of Al2O3 nanoparticles and their dispersed distribution state through the design of reasonable Al content, so that the distance between particles is greater than the free path of electrons, thereby significantly improving the electrical conductivity of the alloy to 100.3IACS, breaking through the bottleneck of the electrical conductivity of Cu-Al2O3 alloy materials produced by the internal oxidation method reaching 100%IACS. If Al is excessive, reverse diffusion is likely to occur during the internal oxidation process. On the one hand, coarse aluminum oxide particles are formed between the crystals, which cannot achieve the effect of dispersed distribution. On the other hand, the distance between the formed Al2O3 is relatively small, and even aggregates, which has a negative effect on the electrical conductivity. If the content is too little, the Al2O3 is too little and cannot play a strengthening role.

[0016] The addition of rare earth elements Ce and La can form high-melting-point intermetallic compounds with impurity elements S, Pb, Bi, P and other impurity elements in the melt that seriously affect the electrical conductivity, making it easy to remove them by floating, thereby improving the electrical conductivity of the alloy.

[0017] Rare earth elements Ce and La are strong deoxidizers. The oxygen dissolved in the alloy melt is easily oxidized and removed. At the same time, rare earth elements Ce and La are easily enriched at the grain boundaries and the surface of powder particles. During the vacuum atomization powder making process, they can preferentially react with trace oxygen in the atomization environment, which can effectively prevent trace oxygen from forming coarse and brittle CuAlO2 on the powder surface or at the grain boundaries, thereby effectively avoiding defects such as microcracks caused by the formation of CuAlO2 in the subsequent processing process, resulting in reduced hot punching performance, plastic toughness and air tightness of the final material. The formed nano-dispersed CeO2 and La2O3 further improve the strength and heat resistance of the alloy.

[0018] The addition of Sr element can avoid the segregation of Al element along the grain boundary and promote its uniform distribution. During the internal oxidation process, Al2O3 particles are evenly distributed at the grain boundary and inside the grain boundary, avoiding the precipitation of coarse Al2O3 particles along the grain boundary during the internal oxidation process, thereby improving the plasticity and strength of the alloy.

[0019] The second aspect of the present invention provides a method for preparing a rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy, comprising the following steps:

[0020] S1: drying the electrolytic copper and melting it in a vacuum furnace, adding Al, Ce, Sr and La in proportion, and melting them evenly to obtain a Cu-Al-Ce-La-Sr alloy melt;

[0021] S2: heating and atomizing the Cu-Al-Ce-La-Sr alloy melt to obtain Cu-Al-Ce-La-Sr alloy powder;

[0022] S3: crushing and sieving the Cu-Al-Ce-La-Sr alloy powder, and taking the powder with a particle size of less than 300 meshes for subsequent steps;

[0023] S4: mixing the Cu-Al-Ce-La-Sr alloy powder and an oxidant and performing internal oxidation treatment to obtain Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0024] S5: performing a first reduction on the Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder to obtain Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder;

[0025] S6: cold isostatically pressing the Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder mixture to obtain an ingot;

[0026] S7: After the billet is reduced for the second time;

[0027] S8: heating and extruding the billet processed in step S7 to obtain a rod;

[0028] S9: Drawing the rod to a preset size.

[0029] A technical solution in the method for preparing rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy of the present invention has at least the following beneficial effects:

[0030] The preparation method of the present invention can significantly improve the electrical conductivity of the alloy by reasonably controlling the addition of rare earth elements and internal oxidation treatment, breaking through the electrical conductivity bottleneck of traditional Cu-Al2O3 alloys. Furthermore, the rare earth elements can effectively remove harmful impurities in the melt and improve the overall electrical conductivity of the alloy. Furthermore, the distribution of nano-scale CeO2 and La2O3 enhances the strength and heat resistance of the alloy while avoiding the formation of microcracks. In addition, the uniform distribution of Al2O3 particles in the alloy improves the plasticity and strength of the alloy, ensuring the high quality of the final product.

[0031] According to some embodiments of the present invention, in step S1, the vacuum degree of melting in the vacuum furnace is 1×10 -1 Pa~1×10 -3 Pa, melting temperature 1180℃~1280℃.

[0032] According to some embodiments of the present invention, in step S2, before atomization, the Cu-Al-Ce-La-Sr alloy melt is heated to 1240° C. to 1280° C. and then atomized by high-purity nitrogen in an atomizing device.

[0033] In step S2, the melt is heated to 1240°C to 1280°C and then atomized with high-purity nitrogen to ensure that the alloy melt is evenly atomized into fine powder particles. This temperature range helps the melt to be completely melted and have appropriate fluidity, avoiding the generation of large particles or uneven powder during the atomization process. The use of high-purity nitrogen can reduce the interference of oxygen, prevent powder oxidation, and ensure the quality of the powder and the performance of the alloy.

[0034] In step S3, the Cu-Al-Ce-La-Sr alloy powder is crushed and sieved, and powder with a particle size of less than 300 mesh is taken to ensure that Cu exists in the state of Cu2O.

[0035] In step S3, the powder is crushed and sieved, and powder with a size less than 300 mesh is selected, which helps to ensure that Cu exists in the state of Cu2O. This is because small-particle powder has a larger specific surface area and can react more effectively with the oxidant, thereby promoting Cu to form Cu2O during the internal oxidation process. Cu2O in this state helps to improve the mechanical properties and electrical conductivity of the final alloy, and can react with other components to optimize the structure and properties of the alloy.

[0036] According to some embodiments of the present invention, in step S4, the temperature of the internal oxidation treatment is 850°C to 950°C.

[0037] According to some embodiments of the present invention, in step S4, the internal oxidation treatment time is 0.3h to 0.8h.

[0038] According to some embodiments of the present invention, in step S4, the internal oxidation is performed under the protection of high-purity nitrogen.

[0039] The main function of the internal oxidation treatment in step S4 is to react the oxidant with the metal in the alloy powder to form stable oxides, such as Al2O3, CeO2, La2O3 and SrO, by controlling the temperature and time. This process is carried out at a high temperature of 850℃ to 950℃, which can ensure the uniform distribution of the oxides and effectively enhance the strength and heat resistance of the alloy. The time is controlled between 0.3h and 0.8h to ensure full reaction while avoiding excessive oxidation. High-purity nitrogen protection can prevent further oxidation of the alloy by oxygen, thereby maintaining the stability of the alloy's performance.

[0040] According to some embodiments of the present invention, in step S4, the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant is 1:0.0004-0.01.

[0041] According to some embodiments of the present invention, in step S4, the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant is 1:0.0004-0.006.

[0042] According to some embodiments of the present invention, in step S4, the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant is any one of 1:0.0004, 1:0.005, 1:0.006, or a range formed by any two of them.

[0043] According to some embodiments of the present invention, in step S5, before the first reduction, the alloy powder is crushed and sieved, and the powder with a particle size of less than 100 mesh is reduced.

[0044] According to some embodiments of the present invention, in step S5, the first reduction is a step-by-step reduction.

[0045] According to some embodiments of the present invention, in step S5, the conditions for the stepwise reduction are 500° C. to 550° C., keeping warm for 0.5 h to 1.5 h, heating to 800° C. to 900° C., and keeping warm for 0.5 h to 1.5 h.

[0046] According to some embodiments of the present invention, in step S5, the gas for the stepwise reduction is high-purity hydrogen with a dew point below -40°C.

[0047] The function of step S5 is to reduce the oxides to metal compounds through step-by-step reduction and restore the metal elements in the alloy powder. First, a preliminary reduction is carried out at 500°C to 550°C to remove some oxides; then the temperature is raised to 800°C to 900°C for further reduction to ensure that the oxides are completely removed. The use of high-purity hydrogen can prevent other gases from interfering with the reduction process, and the dew point is lower than -40°C to ensure that the gas is dry and reduce the impact of moisture on the reduction effect. By crushing and screening powders less than 100 mesh, the uniformity and efficiency of the reduction reaction are improved.

[0048] The process of stepped hydrogen reduction is to first carry out hydrogen reduction at a lower temperature, which can not only remove oxygen but also prevent the powder from sintering together, providing an effective channel for subsequent high-temperature hydrogen reduction and avoiding incomplete reduction.

[0049] According to some embodiments of the present invention, in step S6, during the cold isostatic pressing process, the density of the green compact is controlled within a range of 65% to 75%.

[0050] Controlling the density of the green compact in the cold isostatic pressing process within the range of 65% to 75% helps ensure uniform compaction and density distribution of the powder. This density range can not only maintain sufficient porosity for better reduction and molding in subsequent processing, but also ensure that the green compact has sufficient mechanical strength, reduce internal defects, and improve the quality of the final product.

[0051] According to some embodiments of the present invention, in step S7, the second reduction method comprises: encapsulating the billet pressed in step S6 in a pure copper clad shell with pure copper connecting pipes at both ends, reducing it in a hydrogen reduction furnace, and reducing it under the following conditions: temperature 800°C to 900°C, time 0.5 to 1.5h, sealing one end, and evacuating the vacuum until the vacuum reaches 5×10 - 2 After sealing, seal the other end.

[0052] The second reduction in step S7 is performed by encapsulating the ingot in a copper-clad shell and reducing it with hydrogen at a temperature of 800°C to 900°C, which helps to further remove residual oxides and impurities and improve the purity and performance of the alloy. The encapsulation and vacuuming process can prevent oxygen from re-entering, avoid oxidation reactions, ensure the integrity and consistency of the reduction effect, and improve the quality of the final material.

[0053] According to some embodiments of the present invention, in step S8, the temperature of the heating extrusion molding is 820°C to 880°C.

[0054] According to some embodiments of the present invention, in step S8, the extrusion ratio of the heated extrusion molding is greater than 25:1.

[0055] According to some embodiments of the present invention, in step S9, based on product requirements, for products with air tightness requirements, the preparation method further includes performing a creep aging treatment after the rod is drawn to a preset size.

[0056] According to some embodiments of the present invention, in step S9, the creep aging treatment method includes: placing the rod in a sheath, sealing, evacuating, and aging at 550° C. to 650° C. for 2 h to 4 h at an air pressure of 50 MPa to 70 MPa.

[0057] The specific function of step S9 is to further optimize the performance of the alloy through creep aging treatment. This treatment can improve the air tightness and mechanical strength of the alloy and reduce microcracks and defects. Aging the rod under high pressure and high temperature conditions helps to stabilize the microstructure of the alloy, improve its heat resistance and plastic toughness, and thus meet the product standards with strict requirements on air tightness. DETAILED DESCRIPTION

[0058] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0059] In the first aspect, some embodiments of the present invention provide a rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy, the components of which include:

[0060] Al2O3: 0.01wt%~0.08wt%,

[0061] Ce: 0.01wt%~0.03wt%,

[0062] Sr: 0.01wt%~0.03wt%,

[0063] La: 0.01 wt% to 0.03 wt%,

[0064] The balance is copper and unavoidable impurities.

[0065] It can be understood that the present invention, through the design of reasonable Al content, regulates the volume percentage of Al2O3 nanoparticles and their dispersed distribution state, so that the particle distance is greater than the free path of electrons, thereby significantly improving the electrical conductivity of the alloy to 100.3IACS, breaking through the bottleneck of the electrical conductivity of Cu-Al2O3 alloy materials produced by the internal oxidation method reaching 100%IACS.

[0066] It should be noted that the addition of rare earth elements Ce and La can form high-melting-point intermetallic compounds with impurity elements S, Pb, Bi, P and other impurity elements in the melt that seriously affect the electrical conductivity, which can be easily removed by flotation, thereby improving the electrical conductivity of the alloy.

[0067] Rare earth elements Ce and La are strong deoxidizers. The oxygen dissolved in the alloy melt is easily oxidized and removed. At the same time, rare earth elements Ce and La are easily enriched at the grain boundaries and the surface of powder particles. During the vacuum atomization powder making process, they can preferentially react with trace oxygen in the atomization environment, which can effectively prevent trace oxygen from forming coarse and brittle CuAlO2 on the powder surface or at the grain boundaries, thereby effectively avoiding defects such as microcracks caused by the formation of CuAlO2 in the subsequent processing process, resulting in reduced hot punching performance, plastic toughness and air tightness of the final material. The formed nano-dispersed CeO2 and La2O3 further improve the strength and heat resistance of the alloy.

[0068] It should also be noted that the addition of Sr elements can prevent the Al element from segregating along the grain boundaries and promote its uniform distribution. During the internal oxidation process, Al2O3 particles are evenly distributed at the grain boundaries and inside the grains, avoiding the precipitation of coarse Al2O3 particles along the grain boundaries during the internal oxidation process, thereby improving the plasticity and strength of the alloy.

[0069] In a second aspect, some embodiments of the present invention provide a method for preparing a rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy, comprising the following steps:

[0070] S1: drying the electrolytic copper and melting it in a vacuum furnace, adding Al, Ce, Sr and La in proportion, and melting them evenly to obtain a Cu-Al-Ce-La-Sr alloy melt;

[0071] S2: heating and atomizing the Cu-Al-Ce-La-Sr alloy melt to obtain Cu-Al-Ce-La-Sr alloy powder;

[0072] S3: crushing and sieving the Cu-Al-Ce-La-Sr alloy powder, and taking the powder with a particle size of less than 300 meshes for subsequent steps;

[0073] S4: mixing the Cu-Al-Ce-La-Sr alloy powder and the oxidant and performing internal oxidation treatment to obtain Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0074] S5: performing a first reduction on the Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder to obtain Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder;

[0075] S6: cold isostatically pressing the Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder mixture to obtain an ingot;

[0076] S7: After the billet is reduced for the second time;

[0077] S8: heating and extruding the billet processed in step S7 to obtain a rod;

[0078] S9: Drawing the rod to a preset size.

[0079] It can be understood that the preparation method of the present invention can significantly improve the electrical conductivity of the alloy by reasonably controlling the addition of rare earth elements and internal oxidation treatment, breaking through the conductivity bottleneck of traditional Cu-Al2O3 alloys. Furthermore, rare earth elements can effectively remove harmful impurities in the melt and improve the overall electrical conductivity of the alloy. Furthermore, the distribution of nano-scale CeO2 and La2O3 enhances the strength and heat resistance of the alloy while avoiding the formation of microcracks. In addition, the uniform distribution of Al2O3 particles in the alloy improves the plasticity and strength of the alloy, ensuring the high quality of the final product.

[0080] In combination with the second aspect, in some embodiments of the present invention, in step S1, the vacuum degree of melting in the vacuum furnace is 1×10 -1 Pa~1×10 -3 Pa, melting temperature 1180℃~1280℃.

[0081] In combination with the second aspect, in some embodiments of the present invention, in step S2, before atomization, the Cu-Al-Ce-La-Sr alloy melt is heated to 1240°C to 1280°C, and then atomized by high-purity nitrogen in an atomization device.

[0082] In step S2, the melt is heated to 1240°C to 1280°C and then atomized with high-purity nitrogen to ensure that the alloy melt is evenly atomized into fine powder particles. This temperature range helps the melt to be completely melted and have appropriate fluidity, avoiding the generation of large particles or uneven powder during the atomization process. The use of high-purity nitrogen can reduce the interference of oxygen, prevent powder oxidation, and ensure the quality of the powder and the performance of the alloy.

[0083] In step S3, the Cu-Al-Ce-La-Sr alloy powder is crushed and sieved, and the powder with a particle size of less than 300 mesh is taken for subsequent steps to ensure that Cu exists in the state of Cu2O.

[0084] In step S3, the powder is crushed and sieved, and powder with a size less than 300 mesh is selected as an oxidant, which helps to ensure that Cu exists in the state of Cu2O. This is because small-particle powder has a larger specific surface area and can react more effectively with the oxidant, thereby promoting Cu to form Cu2O during the internal oxidation process. This state of Cu2O helps to improve the mechanical properties and electrical conductivity of the final alloy, and can react with other components to optimize the structure and properties of the alloy.

[0085] In combination with the second aspect, in some embodiments of the present invention, in step S4, the temperature of the internal oxidation treatment is 850°C to 950°C.

[0086] In combination with the second aspect, in some embodiments of the present invention, in step S4, the time of the internal oxidation treatment is 0.3h to 0.8h.

[0087] In combination with the second aspect, in some embodiments of the present invention, in step S4, the internal oxidation is performed under the protection of high-purity nitrogen.

[0088] The main function of the internal oxidation treatment in step S4 is to react the oxidant with the metal in the alloy powder to form stable oxides, such as Al2O3, CeO2, La2O3 and SrO, by controlling the temperature and time. This process is carried out at a high temperature of 850℃ to 950℃, which can ensure the uniform distribution of the oxides and effectively enhance the strength and heat resistance of the alloy. The time is controlled between 0.3h and 0.8h to ensure full reaction while avoiding excessive oxidation. High-purity nitrogen protection can prevent further oxidation of the alloy by oxygen, thereby maintaining the stability of the alloy's performance.

[0089] In combination with the second aspect, in some embodiments of the present invention, in step S4, the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant is 1:0.0004-0.006.

[0090] In combination with the second aspect, in some embodiments of the present invention, in step S4, the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant is any value of 1:0.0004, 1:0.005, 1:0.006, or a range formed by any two of them.

[0091] In combination with the second aspect, in some embodiments of the present invention, in step S5, before the first reduction, the alloy powder is crushed and sieved, and the powder with a particle size of less than 100 mesh is reduced.

[0092] In combination with the second aspect, in some embodiments of the present invention, in step S5, the first reduction is a step-by-step reduction.

[0093] In combination with the second aspect, in some embodiments of the present invention, in step S5, the conditions for the step reduction are 500°C to 550°C, keeping warm for 0.5h to 1.5h, heating to 800°C to 900°C, and keeping warm for 0.5h to 1.5h.

[0094] In combination with the second aspect, in some embodiments of the present invention, in step S5, the gas for the step-by-step reduction is high-purity hydrogen with a dew point below -40°C.

[0095] The function of step S5 is to reduce the oxides to metal compounds through step-by-step reduction and restore the metal elements in the alloy powder. First, a preliminary reduction is carried out at 500°C to 550°C to remove some oxides; then the temperature is raised to 800°C to 900°C for further reduction to ensure that the oxides are completely removed. The use of high-purity hydrogen can prevent other gases from interfering with the reduction process, and the dew point is lower than -40°C to ensure that the gas is dry and reduce the impact of moisture on the reduction effect. By crushing and screening powders less than 100 mesh, the uniformity and efficiency of the reduction reaction are improved.

[0096] The process of stepped hydrogen reduction is to first carry out hydrogen reduction at a lower temperature, which can not only remove oxygen but also prevent the powder from sintering together, providing an effective channel for subsequent high-temperature hydrogen reduction and avoiding incomplete reduction.

[0097] In combination with the second aspect, in some embodiments of the present invention, in step S6, during the cold isostatic pressing process, the density of the pressed green body is controlled within a range of 65% to 75%.

[0098] Controlling the density of the green compact in the cold isostatic pressing process within the range of 65% to 75% helps ensure uniform compaction and density distribution of the powder. This density range can not only maintain sufficient porosity for better reduction and molding in subsequent processing, but also ensure that the green compact has sufficient mechanical strength, reduce internal defects, and improve the quality of the final product.

[0099] In combination with the second aspect, in some embodiments of the present invention, in step S7, the second reduction method comprises: encapsulating the billet pressed in step S6 in a pure copper clad shell with pure copper connecting pipes at both ends, reducing it in a hydrogen reduction furnace, and reducing it under the conditions of: temperature 800°C to 900°C, time 0.5 to 1.5h, sealing one end, and evacuating the vacuum until the vacuum reaches 5×10 -2 After sealing, seal the other end.

[0100] The second reduction in step S7 is performed by encapsulating the ingot in a copper-clad shell and reducing it with hydrogen at a temperature of 800°C to 900°C, which helps to further remove residual oxides and impurities and improve the purity and performance of the alloy. The encapsulation and vacuuming process can prevent oxygen from re-entering, avoid oxidation reactions, ensure the integrity and consistency of the reduction effect, and improve the quality of the final material.

[0101] In combination with the second aspect, in some embodiments of the present invention, in step S8, the temperature of the heating extrusion molding is 820°C to 880°C.

[0102] In combination with the second aspect, in some embodiments of the present invention, in step S8, the extrusion ratio of the heated extrusion molding is greater than 25:1.

[0103] In combination with the second aspect, in some embodiments of the present invention, in step S9, according to product requirements, for products with air tightness requirements, the preparation method also includes performing creep aging treatment after drawing the rod to a preset size.

[0104] In combination with the second aspect, in some embodiments of the present invention, in step S9, the creep aging treatment method includes: placing the rod in a sheath, sealing, evacuating, and aging at 550°C to 650°C for 2h to 4h under an air pressure of 50MPa to 70MPa.

[0105] The specific function of step S9 is to further optimize the performance of the alloy through creep aging treatment. This treatment can improve the air tightness and mechanical strength of the alloy and reduce microcracks and defects. Aging the rod under high pressure and high temperature conditions helps to stabilize the microstructure of the alloy, improve its heat resistance and plastic toughness, and thus meet the product standards with strict requirements on air tightness.

[0106] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0107] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0108] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0109] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0110] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0111] Example 1

[0112] A rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy:

[0113] The alloy composition is Al2O3-0.02wt%, Ce content is 0.015wt%, Sr content is 0.01%, La content is 0.015wt%, and the balance is copper and inevitable impurities.

[0114] The specific preparation method is:

[0115] The electrolytic copper is dried and melted in a vacuum furnace with a vacuum degree of 1×10 -3 Pa, melting temperature 1250℃;

[0116] The obtained Cu-Al-Ce-La-Sr alloy melt is atomized into Cu-Al-Ce-La-Sr alloy powder by using high-purity N2 gas in an atomizing device;

[0117] The Cu-Al-Ce-La-Sr alloy powder obtained by atomization is crushed by jet mill, sieved, and the powder with a particle size of less than 300 mesh is used as internal oxidation alloy powder;

[0118] The Cu-Al-Ce-La-Sr alloy powder obtained by screening is mixed with an oxidant (cuprous oxide), the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant being 1:0.002, and after the ingredients are fully mixed, they are placed in a sealed container, and heated to 900° C. under the protection of high-purity N2 for internal oxidation for 5 hours to form a Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0119] The alloy powder after internal oxidation is crushed and sieved, and the powder with a particle size of less than 100 mesh is taken and reduced in a hydrogen reduction furnace. The reduction conditions are: temperature 500°C, time 1h, then heated to 850°C, time 1.5h; the reduced hydrogen is high-purity hydrogen with a dew point below -40°C;

[0120] The obtained Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder mixture is subjected to cold isostatic pressing, and the density of the pressed green body is controlled at 75%;

[0121] The pressed ingot was encapsulated in a pure copper clad shell with pure copper connecting pipes at both ends and reduced in a hydrogen reduction furnace. The reduction conditions were: temperature 850°C, time 1h; after sealing one end, vacuum was drawn. When the vacuum degree reached 5×10 -3 After Pa, seal the other end; heat the billet obtained in the step to 850°C under high-purity N2 protection conditions, and hot extrude it into a rod; the extrusion ratio during hot extrusion should be 30:1; cold draw the hot extruded rod to the specified size;

[0122] The cold-drawn sample was placed in a bag, sealed, evacuated, and aged at 600°C for 4 h under a pressure of 60 MPa.

[0123] The measured alloy performance data are shown in Table 1.

[0124] Table 1

[0125]

[0126] Example 2

[0127] A rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy:

[0128] The alloy composition is Al2O3-0.023wt%, Ce content is 0.01wt%, Sr content is 0.01wt%, La content is 0.015wt%, and the balance is copper and inevitable impurities.

[0129] The specific preparation method is:

[0130] The electrolytic copper is dried and melted in a vacuum furnace with a vacuum degree of 1×10-3 Pa, melting temperature 1250℃;

[0131] The obtained Cu-Al-Ce-La-Sr alloy melt is atomized into Cu-Al-Ce-La-Sr alloy powder by using high-purity N2 gas in an atomizing device;

[0132] The Cu-Al-Ce-La-Sr alloy powder obtained by atomization is crushed by jet mill, sieved, and the powder with a particle size of less than 300 mesh is used as internal oxidation alloy powder;

[0133] The Cu-Al-Ce-La-Sr alloy powder obtained by screening is mixed with an oxidant (cuprous oxide), the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant being 1:0.002, and after the ingredients are fully mixed, they are placed in a sealed container, and heated to 900° C. under the protection of high-purity N2 for internal oxidation for 5 hours to form a Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0134] The internally oxidized alloy powder was crushed and sieved, and the powder with a particle size of less than 100 mesh was taken and reduced in a hydrogen reduction furnace. The reduction conditions were: temperature 500°C, time 1h, and then heated to 880°C, time 1.5h;

[0135] The reduced hydrogen is high-purity hydrogen with a dew point below -40°C;

[0136] The obtained Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder mixture is subjected to cold isostatic pressing, and the density of the pressed green body is controlled at 75%;

[0137] The pressed ingot was encapsulated in a pure copper clad shell with pure copper connecting pipes at both ends and reduced in a hydrogen reduction furnace. The reduction conditions were: temperature 850°C, time 1h; after sealing one end, vacuum was drawn. When the vacuum degree reached 5×10 -3 After Pa, seal the other end;

[0138] The ingot obtained in the step is heated to 850°C under N2 protection conditions and hot extruded into a rod;

[0139] The extrusion ratio during hot extrusion is 25:1; the hot extruded rod is cold drawn to a specified size;

[0140] The cold-drawn sample was placed in a bag, sealed, evacuated, and aged at 650°C for 4 h under a pressure of 60 MPa.

[0141] The measured alloy performance data are shown in Table 2.

[0142] Table 2

[0143]

[0144] Example 3

[0145] A rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy:

[0146] The alloy composition is Al2O3-0.031wt%, Ce content is 0.01wt%, Sr content is 0.01wt%, La content is 0.02wt%, and the balance is copper and inevitable impurities.

[0147] The specific preparation method is:

[0148] After drying the electrolytic copper, it is melted in a vacuum furnace with a vacuum degree of 1×10-3Pa and a melting temperature of 1250℃;

[0149] The obtained Cu-Al-Ce-La-Sr alloy melt is atomized into Cu-Al-Ce-La-Sr alloy powder by using high-purity N2 gas in an atomizing device;

[0150] The Cu-Al-Ce-La-Sr alloy powder obtained by atomization is crushed by jet mill, sieved, and the powder with a particle size of less than 300 mesh is used as internal oxidation alloy powder;

[0151] The Cu-Al-Ce-La-Sr alloy powder obtained by screening is mixed with an oxidant (cuprous oxide), the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant being 1:0.003, the ingredients are fully mixed, put into a closed container, and heated to 900° C. under the protection of high-purity N2 for internal oxidation for 5 hours to form a Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0152] The internally oxidized alloy powder is crushed and sieved, and the powder with a particle size of less than 100 mesh is taken and reduced in a hydrogen reduction furnace. The reduction conditions are: temperature 500°C, time 1 hour, and then heated to 880°C, time 2 hours; the reduced hydrogen is high-purity hydrogen with a dew point below -40°C;

[0153] The obtained Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder mixture is subjected to cold isostatic pressing, and the density of the pressed green body is controlled at 75%;

[0154] The pressed ingot is encapsulated in a pure copper clad shell with pure copper connecting pipes at both ends, and reduced in a hydrogen reduction furnace. The reduction conditions are: temperature 850°C, time 1h;

[0155] After sealing one end, evacuate the chamber, and when the vacuum reaches 5×10-3Pa, seal the other end;

[0156] The ingot obtained in the step is heated to 850°C under N2 protection conditions and hot extruded into a rod; the extrusion ratio during hot extrusion is 25:1;

[0157] The obtained hot extrusion is formed into a bar and then cold drawn to a specified size;

[0158] The cold-drawn sample was placed in a bag, sealed, vacuumed, and aged at 650°C for 4 h at a pressure of 65 MPa. The alloy performance data are shown in Table 3.

[0159] Table 3

[0160]

[0161] Example 4

[0162] A rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy:

[0163] The alloy composition is Al2O3-0.042wt%, Ce content is 0.01wt%, Sr content is 0.01wt%, La content is 0.01wt%, and the balance is copper and inevitable impurities.

[0164] The specific preparation method is:

[0165] The electrolytic copper is dried and melted in a vacuum furnace with a vacuum degree of 1×10 -3 Pa, melting temperature 1250℃;

[0166] The obtained Cu-Al-Ce-La-Sr alloy melt is atomized into Cu-Al-Ce-La-Sr alloy powder by using high-purity N2 in an atomizing device;

[0167] The Cu-Al-Ce-La-Sr alloy powder obtained by atomization is crushed by jet mill, sieved, and the powder with a particle size of less than 300 mesh is used as internal oxidation alloy powder;

[0168] The Cu-Al-Ce-La-Sr alloy powder obtained by screening is mixed with an oxidant (cuprous oxide), the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant being 1:0.004, and after the ingredients are fully mixed, they are placed in a sealed container, and heated to 900° C. under the protection of high-purity N2 for internal oxidation for 5 hours to form a Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0169] The internally oxidized alloy powder was crushed and sieved, and the powder with a particle size less than 100 mesh was taken and reduced in a hydrogen reduction furnace. The reduction conditions were: temperature 500°C, time 1h, and then heated to 880°C, time 2h;

[0170] The reduced hydrogen is high-purity hydrogen with a dew point below -40°C;

[0171] The obtained Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder mixture is subjected to cold isostatic pressing, and the density of the pressed green body is controlled at 75%;

[0172] The pressed ingot is encapsulated in a pure copper clad shell with pure copper connecting pipes at both ends, and reduced in a hydrogen reduction furnace. The reduction conditions are: temperature 850°C, time 1h;

[0173] After sealing one end, evacuate the vacuum until the vacuum reaches 5×10 -3 After Pa, seal the other end;

[0174] The ingot obtained in the step is heated to 850°C under N2 protection conditions and hot extruded into a rod; the extrusion ratio during hot extrusion is 25:1;

[0175] The obtained hot extrusion is formed into a bar and then cold drawn to a specified size;

[0176] The cold-drawn sample was placed in a bag, sealed, vacuumed, and aged at 650°C for 4 h at a pressure of 65 MPa. The alloy performance data are shown in Table 4.

[0177] Table 4

[0178]

[0179] Example 5

[0180] A rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy:

[0181] The alloy composition is Al2O3-0.011wt%, Ce content is 0.015wt%, Sr content is 0.01%, La content is 0.015wt%, and the balance is copper and inevitable impurities.

[0182] The specific preparation method is:

[0183] The electrolytic copper is dried and melted in a vacuum furnace with a vacuum degree of 1×10 -3 Pa, melting temperature 1250℃;

[0184] The obtained Cu-Al-Ce-La-Sr alloy melt is atomized into Cu-Al-Ce-La-Sr alloy powder by using high-purity N2 gas in an atomizing device;

[0185] The Cu-Al-Ce-La-Sr alloy powder obtained by atomization is crushed by jet mill, sieved, and the powder with a particle size less than 100 mesh is used as internal oxidation alloy powder;

[0186] The Cu-Al-Ce-La-Sr alloy powder obtained by screening is mixed with an oxidant (cuprous oxide), the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant being 1:0.001, the ingredients are fully mixed, put into a closed container, and heated to 900° C. under the protection of high-purity N2 for internal oxidation for 5 hours to form a Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0187] The internally oxidized alloy powder was crushed and sieved, and the powder with a particle size less than 100 mesh was taken and reduced in a hydrogen reduction furnace. The reduction conditions were: temperature 500°C, time 1h, and then heated to 850°C, time 1.5h;

[0188] The reduced hydrogen is high-purity hydrogen with a dew point below -40°C;

[0189] The obtained Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder mixture is subjected to cold isostatic pressing, and the density of the pressed green body is controlled at 75%;

[0190] The pressed ingot is encapsulated in a pure copper clad shell with pure copper connecting pipes at both ends, and reduced in a hydrogen reduction furnace. The reduction conditions are: temperature 850°C, time 1h;

[0191] After sealing one end, evacuate the vacuum until the vacuum reaches 5×10 -3 After Pa, seal the other end;

[0192] The ingot obtained in the step is heated to 850°C under N2 protection conditions and hot extruded into a rod;

[0193] The extrusion ratio during hot extrusion should be 30:1;

[0194] The obtained hot extrusion is formed into a bar and then cold drawn to a specified size;

[0195] The cold-drawn sample was placed in a bag, sealed, evacuated, and aged at 600°C for 4 h under a pressure of 60 MPa.

[0196] The measured alloy performance data are shown in Table 7.

[0197] Table 7

[0198]

[0199]

[0200] Comparative Example 1 (Al2O3 less than 0.01wt%)

[0201] A rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy:

[0202] The alloy composition is Al2O3-0.008wt%, Ce content is 0.012wt%, Sr content is 0.01%, La content is 0.010wt%, and the balance is copper and inevitable impurities.

[0203] The specific preparation method is:

[0204] The electrolytic copper is dried and melted in a vacuum furnace with a vacuum degree of 1×10 -3 Pa, melting temperature 1250℃;

[0205] The obtained Cu-Al-Ce-La-Sr alloy melt is atomized into Cu-Al-Ce-La-Sr alloy powder by using high-purity N2 gas in an atomizing device;

[0206] The Cu-Al-Ce-La-Sr alloy powder obtained by atomization is crushed by jet mill, sieved, and the powder with a particle size less than 100 mesh is used as internal oxidation alloy powder;

[0207] The Cu-Al-Ce-La-Sr alloy powder obtained by screening is mixed with an oxidant, the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant is 1:0.007, the ingredients are fully mixed, put into a closed container, and heated to 900° C. under the protection of high-purity N2 for internal oxidation for 5 hours to form Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0208] The alloy powder after internal oxidation is crushed and sieved, and the powder with a particle size of less than 100 mesh is taken and reduced in a hydrogen reduction furnace. The reduction conditions are: temperature 500°C, time 1h, then heated to 850°C, time 1.5h; the reduced hydrogen is high-purity hydrogen with a dew point below -40°C;

[0209] The obtained Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder mixture is subjected to cold isostatic pressing, and the density of the pressed green body is controlled at 75%;

[0210] The pressed ingot is encapsulated in a pure copper clad shell with pure copper connecting pipes at both ends, and reduced in a hydrogen reduction furnace. The reduction conditions are: temperature 850°C, time 1h;

[0211] After sealing one end, evacuate the vacuum until the vacuum reaches 5×10 -3 After Pa, seal the other end;

[0212] The ingot obtained in the step is heated to 850°C under N2 protection conditions and hot extruded into a rod;

[0213] The extrusion ratio during hot extrusion should be 30:1; the hot extruded bar is cold drawn to the specified size;

[0214] The cold-drawn sample was placed in a bag, sealed, evacuated, and aged at 600°C for 4 h under a pressure of 60 MPa. The alloy performance data are shown in Table 5.

[0215] Table 5

[0216]

[0217] Comparative Example 2 (Al2O3 greater than 0.08wt%)

[0218] A rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy:

[0219] The alloy composition is Al2O3-0.12wt%, Ce content is 0.015wt%, Sr content is 0.01%, La content is 0.015wt%, and the balance is copper and inevitable impurities.

[0220] The specific preparation method is:

[0221] The electrolytic copper is dried and melted in a vacuum furnace with a vacuum degree of 1×10 -3 Pa, melting temperature 1250℃;

[0222] The obtained Cu-Al-Ce-La-Sr alloy melt is atomized into Cu-Al-Ce-La-Sr alloy powder by using high-purity N2 gas in an atomizing device;

[0223] The Cu-Al-Ce-La-Sr alloy powder obtained by atomization is crushed by jet mill, sieved, and the powder with a particle size of less than 300 mesh is used as internal oxidation alloy powder;

[0224] The Cu-Al-Ce-La-Sr alloy powder obtained by screening is mixed with an oxidant (cuprous oxide), the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant being 1:0.01, the ingredients are fully mixed, put into a closed container, and heated to 900° C. under the protection of high-purity N2 for internal oxidation for 5 hours to form a Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0225] The internally oxidized alloy powder was crushed and sieved, and the powder with a particle size less than 100 mesh was taken and reduced in a hydrogen reduction furnace. The reduction conditions were: temperature 500°C, time 1h, and then heated to 850°C, time 1.5h;

[0226] The reduced hydrogen is high-purity hydrogen with a dew point below -40°C;

[0227] The obtained Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder mixture is subjected to cold isostatic pressing, and the density of the pressed green body is controlled at 75%;

[0228] The pressed ingot is encapsulated in a pure copper clad shell with pure copper connecting pipes at both ends, and reduced in a hydrogen reduction furnace. The reduction conditions are: temperature 850°C, time 1h;

[0229] After sealing one end, evacuate the vacuum until the vacuum reaches 5×10 -3 After Pa, the other end is sealed; the billet obtained in the step is heated to 850°C under N2 protection conditions and hot extruded into a rod;

[0230] The extrusion ratio during hot extrusion should be 30:1; the hot extruded bar is cold drawn to the specified size;

[0231] The cold-drawn sample was placed in a bag, sealed, evacuated, and aged at 600°C for 4 h under a pressure of 60 MPa.

[0232] The measured alloy performance data are shown in Table 6.

[0233] Table 6

[0234]

[0235] Comparative Example 3 (using one-step high temperature reduction)

[0236] A rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy:

[0237] The alloy composition is Al2O3-0.08wt%, Ce content is 0.01wt%, Sr content is 0.015wt%, La content is 0.01wt%, and the balance is copper and inevitable impurities.

[0238] The specific preparation method is:

[0239] The electrolytic copper is dried and melted in a vacuum furnace with a vacuum degree of 1×10 -3 Pa, melting temperature 1250℃;

[0240] The obtained Cu-Al-Ce-La-Sr alloy melt is atomized into Cu-Al-Ce-La-Sr alloy powder by using high-purity N2 gas in an atomizing device;

[0241] The Cu-Al-Ce-La-Sr alloy powder obtained by atomization is crushed by jet mill, sieved, and the powder with a particle size less than 100 mesh is used as internal oxidation alloy powder;

[0242] The Cu-Al-Ce-La-Sr alloy powder obtained by screening is mixed with an oxidant (cuprous oxide), the mass ratio of the Cu-Al-Ce-La-Sr alloy powder to the oxidant being 1:0.007, and after the ingredients are fully mixed, they are placed in a sealed container, and heated to 900° C. under the protection of high-purity N2 for internal oxidation for 5 hours to form a Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder;

[0243] The internally oxidized alloy powder was crushed and sieved, and the powder with a particle size of less than 100 mesh was taken and reduced in a hydrogen reduction furnace. The reduction conditions were: temperature 880°C, time 3h;

[0244] The reduced hydrogen is high-purity hydrogen with a dew point below -40°C;

[0245] The obtained Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder mixture is subjected to cold isostatic pressing, and the density of the pressed green body is controlled at 75%;

[0246] The pressed ingot is encapsulated in a pure copper clad shell with pure copper connecting pipes at both ends, and reduced in a hydrogen reduction furnace. The reduction conditions are: temperature 850°C, time 1h;

[0247] After sealing one end, evacuate the vacuum until the vacuum reaches 5×10 -3 After Pa, the other end is sealed; the billet obtained in the step is heated to 850°C under N2 protection conditions and hot extruded into a rod, with an extrusion ratio of 25:1 during hot extrusion;

[0248] The obtained hot extrusion is formed into a bar and then cold drawn to a specified size;

[0249] The cold-drawn sample was placed in a bag, sealed, evacuated, and aged at 650°C for 4 h under a pressure of 65 MPa.

[0250] The measured alloy performance data are shown in Table 8.

[0251] Table 8

[0252]

[0253] One-step reduction often uses high-temperature hydrogen annealing (one-step low-temperature hydrogen annealing is not enough to reduce all the oxygen in the alloy powder). At high temperatures, the powders are easily sintered together, which will reduce the area of ​​the inner layer powder contacting hydrogen and cause insufficient reduction.

[0254] The present invention controls the volume percentage of Al2O3 nanoparticles and their dispersion distribution state through the design of reasonable Al content, so that the particle spacing is greater than the free path of electrons, thereby significantly improving the electrical conductivity of the alloy, reaching 100.3IACS, breaking through the bottleneck of the electrical conductivity of Cu-Al2O3 alloy materials produced by the internal oxidation method reaching 100%IACS. It should be noted that at present, none of them has reached 100%IACS ("IACS" stands for "International Annealed Copper Standard", which is a standard used to measure and compare the electrical conductivity of conductors. "100%IACS" means that the electrical conductivity of a certain material is equal to that of international annealed pure copper. When the annealed pure copper matrix is ​​purified and the impurity content is very small, it is possible to exceed 100%IACS. The IACS expression is widely used in the fields of material science and electrical engineering, especially in describing the electrical properties of alloys or other non-pure copper materials). As a non-pure copper material, it is almost impossible for Cu-Al2O3 alloy materials to reach 100%IACS. The present invention makes the Cu-Al2O3 alloy material reach or even exceed the effect of pure copper by purifying the substrate and effectively controlling the Al2O3 spacing.

[0255] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy, characterized in that the components include: Al2O3: 0.01wt%~0.08wt%, Ce: 0.01wt%~0.03wt%, Sr: 0.01wt%~0.03wt%, La: 0.01 wt% to 0.03 wt%, The balance is copper.

2. The method for preparing the rare earth doped Cu-Al2O3 nano-dispersion strengthened alloy according to claim 1, characterized in that: The following steps are involved: S1: drying the electrolytic copper and melting it in a vacuum furnace, adding Al, Ce, Sr and La in proportion, and melting them evenly to obtain a Cu-Al-Ce-La-Sr alloy melt; S2: heating and atomizing the Cu-Al-Ce-La-Sr alloy melt to obtain Cu-Al-Ce-La-Sr alloy powder; S3: crushing and sieving the Cu-Al-Ce-La-Sr alloy powder, and taking the powder with a particle size of less than 300 meshes for subsequent steps; S4: mixing the Cu-Al-Ce-La-Sr alloy powder and an oxidant and performing internal oxidation treatment to obtain Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder; S5: performing a first reduction on the Cu-CuO-Al2O3-CeO2-La2O3-SrO alloy powder to obtain Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder; S6: cold isostatically pressing the Cu-Cu-Al2O3-CeO2-La2O3-SrO alloy powder mixture to obtain an ingot; S7: After the billet is reduced for the second time; S8: heating and extruding the billet processed in step S7 to obtain a rod; S9: Drawing the rod to a preset size.

3. The preparation method according to claim 2, characterized in that: In step S1, the vacuum degree of melting in the vacuum furnace is 1×10 -1 Pa~1×10 -3 Pa, melting temperature 1180℃~1280℃.

4. The preparation method according to claim 2, characterized in that: In step S2, before atomization, the Cu-Al-Ce-La-Sr alloy melt is heated to 1240° C. to 1280° C., and then atomized by high-purity nitrogen in an atomization device.

5. The preparation method according to claim 2, characterized in that: In step S4, the temperature of the internal oxidation treatment is 850° C. to 950° C.; and / or, the time of the internal oxidation treatment is 0.3 h to 0.8 h; and / or, the internal oxidation is carried out under the protection of high-purity nitrogen.

6. The preparation method according to claim 2, characterized in that: In step S5, before the first reduction, the alloy powder is crushed and sieved, and the powder with a particle size of less than 100 mesh is taken for reduction; and / or, the first reduction is a step reduction; and / or, the conditions of the step reduction are 500°C to 550°C, kept warm for 0.5h to 1.5h, heated to 800°C to 900°C, and kept warm for 0.5h to 1.5h; and / or, the gas for the step reduction is high-purity hydrogen with a dew point below -40°C.

7. The preparation method according to claim 2, characterized in that: In step S6, during the cold isostatic pressing process, the density of the green compact is controlled within a range of 65-75%.

8. The preparation method according to claim 2, characterized in that: In step S7, the second reduction method includes: encapsulating the billet pressed in step S6 in a pure copper clad shell with pure copper connecting pipes at both ends, reducing it in a hydrogen reduction furnace, and reducing it under the following conditions: temperature 800°C to 900°C, time 0.5 to 1.5h, sealing one end, and evacuating the vacuum until the vacuum reaches 5×10 -2 After sealing, seal the other end.

9. The preparation method according to claim 2, characterized in that: In step S8, the temperature of the heating extrusion molding is 820°C to 880°C; and / or the extrusion ratio of the heating extrusion molding is greater than 25:

1.

10. The preparation method according to claim 2, characterized in that: The preparation method further comprises performing a creep aging treatment after drawing the rod to a preset size; And / or, the creep aging treatment method includes: placing the rod in a sheath, sealing, evacuating, and aging at 550° C. to 650° C. for 2 h to 4 h at an air pressure of 50 MPa to 70 MPa.